The Art in Introducing Self: I am … rrr… - Wicaksono, Julien Arief; Taufan, Gullit Tornado (Journal of English in Academic and Professional Communication, 2019)
This study analyzed the distinctive categories used in describing oneself written in English by second semester Indonesian students of non-English department, namely agriculture. They are found to be categorized as: 1) name; 2) hometown; 3) character and physical appearance; 4) favourite food, beverages or activity; 5) age; and 6) academic information. In findings, the students tended to mention their unseen aspects rather than their physical appearance which are actually more important and easy to be noticed.Keywords: describing, introducing oneself, non-English students.